Quantifying vertebrate zoogeographical regions of Australia using geospatial turnover in the species composition of mammals, birds, reptiles and terrestrial amphibians - Bein, Bernhard; Ebach, Malte C.; Laffan, Shawn W.; Murphy, Daniel J.; Cassis, Gerasimos (Zootaxa, 2020)
A geospatial analysis of 1,906,302 records of 1938 species of Australian vertebrates has shown that the original regions proposed in the 19th century, namely the Eyrean, Torresian and Bassian still hold. The analysis has shown that the Eyrean region has an east-west divide, forming two, possibly independent arid regions (Eastern Desert and Western Desert provinces), that are shaped by topography and rainfall. A revised and interim zoogeographical area taxonomy of the Australian region is presented herein.